3(2x-6)=4(x+2)

Simple and best practice solution for 3(2x-6)=4(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-6)=4(x+2) equation:


Simplifying
3(2x + -6) = 4(x + 2)

Reorder the terms:
3(-6 + 2x) = 4(x + 2)
(-6 * 3 + 2x * 3) = 4(x + 2)
(-18 + 6x) = 4(x + 2)

Reorder the terms:
-18 + 6x = 4(2 + x)
-18 + 6x = (2 * 4 + x * 4)
-18 + 6x = (8 + 4x)

Solving
-18 + 6x = 8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-18 + 6x + -4x = 8 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-18 + 2x = 8 + 4x + -4x

Combine like terms: 4x + -4x = 0
-18 + 2x = 8 + 0
-18 + 2x = 8

Add '18' to each side of the equation.
-18 + 18 + 2x = 8 + 18

Combine like terms: -18 + 18 = 0
0 + 2x = 8 + 18
2x = 8 + 18

Combine like terms: 8 + 18 = 26
2x = 26

Divide each side by '2'.
x = 13

Simplifying
x = 13

See similar equations:

| 2w+2(4x-7)=86 | | 7m+12/8=2m-1/3 | | 4p^2=-9p-2 | | 3x-1+x+x=6.4 | | 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 | | 8+3m-3=9m+12-5m | | 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 | | 5x+35=86 | | 13=3(x-4)-(x-9) | | 76+6x=-11x-145 | | G(x)=2x+1 | | 0.5x+1.9=0.8x-0.2 |

Equations solver categories